Balloon-borne measurements of aerosol, condensation nuclei, and cloud particles in the stratosphere at McMurdo Station, Antarctica, during the spring of 1987 - Hofmann, D. J.; Rosen, J. M.; Harder, J. W.; Hereford, J. V. (1989)
Measurements of the vertical profile of particles with condensation nuclei counters and eight channel aerosol detectors at McMurdo Station, Antarctica, in 1987 verified observations made in 1986 concerning the absence of upwelling in the polar vortex and the presence of a condensation nuclei layer in conjunction with the ozone hole region. New observations of a bimodal aerosol size distribution, consisting of a large-particle mode mixed in with the small-particle sulfate mode, at temperatures below -79 C are consistent with the presence of nitric acid-water particles at low concentrations. Higher concentrations of large particles were observed in association with nacreous clouds. An unusual particle layer which contained enhanced concentrations of both the small-particle (sulfate) mode and the large-particle (nitric acid) mode was detected at temperatures below -85 C, suggesting simultaneous nucleation and growth phenomena. The vortex condensation nuclei layer was observed to form at the same time as the ozone hole, indicating that formation of the layer is triggered by photochemical processes and may be important in controlling ozone depletion above 22 km.